A3_8 Injecting particles into the atmosphere - Davenport, Liam; Durant, Emile; Cullis, Paul Michael (Physics Special Topics, 2012)
This paper investigates size restrictions on potential particles that could be injected into the atmosphere to absorb some of the solar spectrum, the purpose in mind being to reverse the effects of the loss of ozone. It finds that, were they above the micron length scale, they would be unlikely to remain in the atmosphere for any considerable length of time.